Completion of S-55 Using GIS: A Practical Planning Tool - Parra, Rafael Ricardo Torres (The International Hydrographic Review, 2005)
IHO Publication S-55 ‘Status of Hydrographic Surveying and Nautical Charting Worldwide’, is a most important publication of the International Hydrographic Organization (IHO) and is designed to provide a diagnosis of hydrographic requirements, due to the complete database on international hydrographic knowledge that it contains. This paper presents a methodology proposed by Colombia to calculate the status of the hydrographic surveys and nautical chart availability utilising a Geographic Information System (GIS), a methodology that may be used as a guide for any country determining the information needed for S-55. It was found that following this methodology the way, in which calculations of hydrographic capabilities are determined, may be standardised, and the result can provide an important planning tool to optimise the investment of hydrographic resources at a national and regional level.